Artificial Intelligence in Education: Bibliometric and Systematic Literature Review from 2019 – 2024 - Suryanti, Ristyana; Jahidin, Jaja; Fadlil, Muhammad (International Education Trend Issues, 2024)
In the industrial age of 5.0, technology can be used to make it easier for humans to do their everyday work. The development of information technology today is proven by the emergence of artificial intelligence (AI). Research related to AI in the field of education to this day still continues to be studied and researched. Therefore, there is a need for a literary study to find out the trends of research on artificial intelligence in the field of education in order to facilitate further researchers in determining the themes of their research. This research aims to collect, identify, evaluate, analyze, interpret, and conclude similar research that deals with artificial intelligence in education. The research method uses library study with bibliometric analysis and SLR techniques. The results of this research are divided into four sections according to the research questions studied in 98 articles relevant to research topics. The four components are the benefits of AI, the application of artificial intelligence, the positive and negative impacts of AI, and the challenges to be faced with AI.